2019
DOI: 10.1088/1361-6560/ab3242
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of quantitative accuracy for deep learning based denoising in oncological PET

Abstract: Reducing radiation dose is important for PET imaging. However, reducing injection doses causes increased image noise and low signal-to-noise ratio (SNR), subsequently affecting diagnostic and quantitative accuracies. Deep learning methods have shown a great potential to reduce the noise and improve the SNR in low dose PET data.In this work, we comprehensively investigated the quantitative accuracy of small lung nodules, in addition to visual image quality, using deep learning based denoising methods for oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 47 publications
3
84
1
Order By: Relevance
“…There are several novel aspects of this study. The majority of other related work has been performed in 2D since processing times are faster, fewer GPU memory issues are encountered, and the availability of pretrained 2D networks provides additional options in the choice of training objectives [23][24][25][26]. However, volumetric 3D PET data are the medical standard, and inclusion of the additional dimension of data was expected to improve training stability and robustness of the network performance [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several novel aspects of this study. The majority of other related work has been performed in 2D since processing times are faster, fewer GPU memory issues are encountered, and the availability of pretrained 2D networks provides additional options in the choice of training objectives [23][24][25][26]. However, volumetric 3D PET data are the medical standard, and inclusion of the additional dimension of data was expected to improve training stability and robustness of the network performance [27].…”
Section: Discussionmentioning
confidence: 99%
“…The noise in PET images is generally assumed to follow Gaussian and/or Poisson distributions, and deep learning is especially well positioned to address this since the characteristic features of the noise, regardless of the assumed model, are inherently learned through training. Several techniques have previously been applied successfully for denoising PET images [23][24][25][26], to date however, there are very few studies exploring CNNs which handle 3D data. Due to the volumetric nature of data, it is expected that the performance of CNNs could be improved [27].…”
Section: Introductionmentioning
confidence: 99%
“…By communicating these times to patients can result in enhanced patient satisfaction, and it also helps to identify process improvement opportunities diligently; therefore, augment the number of tests accomplished by any resource [19]. At the time of point of care for medical decision support in requests for imaging, AI algorithms can be used to scrutinize a patient's medical records and decide the suitableness of imaging and provide advice for which imaging exam would be most appropriate [20]. Some AI systems have demonstrated assurance in de-noising data obtained at notably lower radiation levels than previously required, resulting in image acquisition optimization with dramatically low radiation exposure [21].…”
Section: Ai Affecting Radiologymentioning
confidence: 99%
“…Lu et al utilized various networks, such as CAE, 2D U-Net, 2.5D U-Net, 3D U-Net, and GAN, to predict standard-dose brain PET images from low-dose PET images. 26 Their results showed that optimal deep learning networks are task-based and differ depending on the desired application. Furthermore, their studies showed comparable visual image quality between CAE, U-Net (2.5D and 3D), and GAN.…”
Section: Modelmentioning
confidence: 99%
“…Both models were trained on 35 subjects with leaveone-out cross validation. For non-CNN-based denoising methods, we applied a 3D 5-mm FWHM Gaussian filtering method 25,26 and compared it to both CNN models. Comparison of these three models was evaluated through objective imaging metrics: PSNR, SSIM, and MAPE.…”
Section: Introductionmentioning
confidence: 99%